Pos on Employee Engagement with Job Satisfiaction as a Mediating Variable - Duratul Fakhria; Hendrik Heri Sandi (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This research explores how Perceived Organizational Support influences. Employee Engagement, considering Job Satisfaction as a mediating factor, in the context of employees working for Trans Padang a key provider of public transportation services in the city of Padang. The focus of this research study is to examine the relationships among perceived organizational support, job satisfaction, and employee engagement. Using a total sample technique, a quantitative research design was used, and 48 employees participated as respondents. data were gathered through the distribution of questionnaires, and the analysis was conducted using Partial Least Squares (PLS) approach within the Structural Equation Modeling (SEM) framework. The findings indicate that POS has a positive and significant influence on both Employee Engagement and Job Satisfaction. In addition, Job Satisfaction has a positive effect on Employee Engagement. Furthermore, Job Satisfaction was found to be a significant and positive mediating variable in the connection between POS and EE.